Glasswing‐Butterfly‐Inspired Multifunctional Scleral Lens and Smartphone Raman Spectrometer for Point‐of‐Care Tear Biomarker Analysis. Issue 5 (1st December 2022) - Narasimhan, Vinayak; Siddique, Radwanul Hasan; Kim, Un Jeong; Lee, Suyeon; Kim, Hyochul; Roh, YoungGeun; Wang, Yibing Michelle; Choo, Hyuck
Abstract: Augmenting contact lenses with sensing capabilities requires incorporating multiple functionalities within a diminutive device. Inspired by multifunctional biophotonic nanostructures of glasswing butterflies, a nanostructured scleral lens with enhanced optical, bactericidal, and sensing capabilities is reported. When used in conjunction with a smartphone‐integrated Raman spectrometer, the feasibility of point‐of‐care applications is demonstrated. The bioinspired nanostructures made on parylene films are mounted on the anterior and posterior side of a scleral lens to create a nanostructured lens. Compared to unstructured parylene, nanostructured parylene minimizes glare by 4.3‐fold at large viewing angles up to 80 o . When mounted on a scleral lens, the nanostructures block 2.8‐fold more ultraviolet (UVA) light while offering 1.1‐fold improved transmission in the visible regime. Furthermore, the nanostructures exhibit potent bactericidal activity against Escherichia coli, killing 89% of tested bacteria within 4 h. The same nanostructures, when gold‐coated, are used to perform rapid label‐free multiplex detection of lysozyme and lactoferrin, the protein biomarkers of the chronic dry eye disease, in whole human tears using drop‐coating deposition Raman spectroscopy. The detection of both proteins in whole human tear samples from different subjects using the nanostructured lens produced excellent correlation with commercial enzyme‐based assays while simultaneously displaying a 1.5‐fold lower standard deviation. Abstract : This work reports a multifunctional bioinspired nanostructured scleral lens. Inspired by biophotonic nanostructures on glasswing butterflies, bioinspired nanostructures made on parylene films are mounted on a scleral lens for enhanced optical, bactericidal, and sensing capabilities. The scleral lens sensor is used to detect lysozyme and lactoferrin in whole human tears for chronic dry eye disease management.